Change Management in Improving Organizational Quality - Maya Amelia; Nuri Aslami (Fakultas Ekonomi Universitas Dehasen Bengkulu, 2022)
Change is a life phenomenon and cannot be avoided by humans, change exists so that we live better. Organizations must experience change because of the desire for organizational growth to occur. So that the organization or company is expected that what is cultivated or managed can continue to grow and develop. Thissstudyyaims to determine how change management in improving the quality of the organization. The method used in this research is the literature study method, namely the method of data collection directed at searching for data and information through documents, theoretical studies, references, collections of articles, journals and books from all forms of sources related to the subject matter. The results of this study indicate that organizations need to implement change management through change management to increase organizational effectiveness and without being managed properly, change will not achieve the expected results